(untitled) (Communications in Computational Physics, 2020)
Fluctuations in log-amplitude and travel time of teleseismic P waves recorded by the EarthScope USArray are used to invert for the heterogeneity spectrum of P-wave velocity in a 1000 km thick region of the upper mantle beneath the array. These fluctuations are used to form coherence functions. Best fits to joint transverse coherence functions require a depth dependent heterogeneity spectrum, with peaks in narrow depth ranges. These peaks agree well with peaks predicted for the temperature derivative of seismic velocity from models of the chemistry and phase of silicate mineral assemblages appropriate for the upper mantle, correlating with the depths of phase changes. The results show that chemistry and phase act in concert with lateral and depth variations in temperature to produce the observed heterogeneity in seismic velocities in the upper mantle at spatial scales from 50 to 300 km.